2021
DOI: 10.3233/jad-201110
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Safety in the Context of Dementia: A Multiperspective Qualitative Study

Abstract: Background: Current research acknowledges the relevance of the emotional safety of people living with dementia. However, available evidence regarding this topic is limited. A comprehensive view of this topic that equally considers the perspectives of people living in an early stage of dementia, relatives, and public stakeholders is lacking. Objective: This study aimed to obtain a multiperspective view of emotional safety in the context of dementia in the living environment. Methods: A descriptive qualitative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Coexisting with anomie also involved unsettled feelings of helplessness, self‐deprecation, and fear, which increased stress and a desire for isolation. Negative emotions can result in a cycle of negative feedback that is not productive for individuals navigating early symptoms of dementia (Kuske et al., 2021). An interpretive qualitative meta‐synthesis found that providing PLWD with emotion‐focused coping strategies could help reduce stress associated with negative emotions in early dementia (Bjørkløf et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Coexisting with anomie also involved unsettled feelings of helplessness, self‐deprecation, and fear, which increased stress and a desire for isolation. Negative emotions can result in a cycle of negative feedback that is not productive for individuals navigating early symptoms of dementia (Kuske et al., 2021). An interpretive qualitative meta‐synthesis found that providing PLWD with emotion‐focused coping strategies could help reduce stress associated with negative emotions in early dementia (Bjørkløf et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the interviewees first filled out the informed consent forms and were informed that they could exit the interview at any time. The researcher applied the probability and purposeful sampling method for selecting the experts [31,32] In the present study, the theoretical saturation approach was used to end the interview; in this approach, the researcher immediately analyzed the interviews and performed the next one based on the output of the previous interview [33][34][35]. In this regard, the researcher attained theoretical saturation after 12 interviews.…”
Section: Qualitative Studymentioning
confidence: 99%